John Steinbeck at the Italica roman ruins in Seville, Spain (Spain; Seville, 2022)
John Steinbeck at the Italica roman ruins in Seville, Spain. Italica lies 9 km northwest of Seville in southern Spain, was a settlement founded by the Roman general Scipio in the province of Hispania Baetica. It was the birthplace of Emperors and flourished under the reign of Hadrian, becoming an elaborate urban center and obtaining the highest status of Roman city. Original in safe.